POTENSI POHON PENGHASIL GAHARU BUDIDAYA DI KABUPATEN KAMPAR PROVINSI RIAU - Prastyaningsih, Sri Rahayu; Ervayenri, Ervayenri; Azwin, Azwin (Wahana Forestra: Jurnal Kehutanan, 2015)
Scarcity of agarwood trees in natural forests cause agarwood trade of all species be included Aquilaria malacensis into CITIES (Convention on International trade in Endangered Species of Wild Fauna and Flora) and limited exsport quota. Agarwood is a resinous wood and has the benefit of such ingredients as perfumes and medicines. High economic value of Eaglewood cause increased community interest for cultivation of Gaharu plants. This research was done in January to March 2015 in Pangkalan Baru, Siak Hulu subdistrict and Kuapan, Tambang subdistrict, Kampar district, Riau Province. The materials used were map, related research, camera , GPS, compass, altimeter, measuring tape, hagameter, talysheet, etc. Field of observations with searching information about cropping in cultivation of agarwood, identification of farmers and cropping patterns. Survey of agarwood tree conducted by purposive sampling method. Data obtained by making a plot with measuring 20 x 20 m plated on transect with sampling intensity by 20%. The results of research on cropping pattern was monoculture and multiculture. Multiculture was in the rubber plants. The age of agarwood trees in monokultur was 19 years old., whereas multiculture between 2-5 year. Potential agarwood trees in monocultural was 19 mÂ³ but multicultue can not be due to plant cause age>5 years.